Character Education Concepts in Ihya' Ulumuddin - Arri Salaeh; Nawawee Saha; Nurul Khair; Djabir Abdoulaye Djabir; Popoola Kareem Hamed (Southeast Asian Journal of Islamic Education, 2023)
This research is motivated by moral decline in the current era of globalization, within the family, school, and community. Education has an essential role in rebuilding individual character values. Imam Al-Ghazali's character education concepts in Ihya’ Ulumuddin are fascinating because of the many character values reflected and discussed. This study uses a type of library research with a qualitative approach. Primary and secondary data are obtained, collected, and processed through re-examination (editing), organizing the data, and finding the results, then re-analyzed using content analysis techniques to know the benefits, marks, or effects. The conclusion that can be drawn from this research is that the concept of character education for Imam Al-Ghazali has two main elements: soul character, which is reflected in sincere worship for God, and physical character, which is reflected in good morals and deepening helpful knowledge. These two characters encourage a person to have a clean heart by continuously doing good for the happiness of oneself and others. Characters emerge that connect us with Allah S.W.T. and other people, such as the character of discipline in praying five times a day and in carrying out work, working hard and independently in all activities, being responsible and respecting the rights of others, being friendly and communicative in socializing, and love peace and love for our beloved motherland.